Sustainability of the Healthy Rice Plantation Program in Klungkung Village, Sukorambi Subdistrict, Jember Regency - Pramesti, Shafa Jane; Prayuningsih, Henik; Aulia, Anisa Nurina (Universitas Muhammadiyah Jember, 2024)
Healthy rice is a solution to the problems and challenges in rice farming faced in the Sukorambi District area to increase yields without damaging the ecosystem. This study aims to determine the driving factors and inhibitors of the sustainability of healthy rice programs in Sukorambi District, Jember Regency. This research uses the Force Field Analysis (FFA) method with a total sample of 20 healthy rice farmers from 6 farmer groups in Sukorambi District. The selection of locations in Sukorambi District with consideration to encourage farmers to apply environmentally friendly healthy rice cultivation in Sukorambi District. The results showed that: (1) Assistance by PPL obtained the highest TNB as a driving factor for the sustainability of the healthy rice program, namely 2.04% (2) The length of time required to make organic fertilizer obtained the highest TNB as an inhibiting factor. Farmers together with farmer groups need to maximize assistance by PPL and minimize the time to make organic fertilizer. To realize the sustainability of the healthy rice program, it is recommended to maintain assistance by PPL on a regular basis and design an organic fertilizer composition that has a faster production process.